Staying connected while physically apart: Digital communication when face-to-face interactions are limited. (September 2022) - Nguyen, Minh Hao; Gruber, Jonathan; Marler, Will; Hunsaker, Amanda; Fuchs, Jaelle; Hargittai, Eszter
Theoretical and empirical work on digital media use and social connectedness has often considered face-to-face communication to be an available option. But how do various digital media uses relate to social connectedness when face-to-face communication is not, or much less, possible? Drawing on survey data from 2925 US adults during the early months of the COVID-19 pandemic, we find that different digital communication methods display different relationships with social connectedness under stay-at-home circumstances with limited in-person interactions outside the home. Overall, digital communication relates to lower social connectedness. In line with notions from social presence theory, especially digital media lower in social presence (e.g. email, social media, and online games, and to some extent text messaging) relate negatively to social connectedness, while this is not the case for higher social presence media (e.g. voice and video calls). Our study has implications for theorizing about digital media use and social connectedness in times when face-to-face communication is less available.